Periodicity of Thalamic Spindle Waves Is Abolished by ZD7288,a Blocker of I h - Lüthi, Anita; Bal, Thierry; McCormick, David A. (The Review of Economics and Statistics, 1998)
The actions of the novel bradycardiac agent ZD7288 [4-(N-ethyl-N-phenylamino)-1, 2-dimethyl-6-(methylamino)pyrimidinium chloride] were investigated on the hyperpolarization-activated cation current Ih and on network activity in spontaneously spindling ferret lateral geniculate (LGNd) slices in vitro using intracellular recording techniques. In voltage-clamp recordings, local application of ZD7288 (1 mM in micropipette) resulted in a complete block of Ih, whereas in current-clamp recordings, application of this agent resulted in an abolition of the depolarizing sag activated by hyperpolarization and decreased the frequency of intrinsic delta-oscillations for which Ih acts as a pacemaker current. In addition, block of Ih with ZD7288 resulted in an abolition of the afterdepolarization (ADP) that follows repetitive hyperpolarization and rebound burst firing as well as that occurring in between spindle waves. The block of the ADP was associated with a block of the spindle wave refractory period such that continuous 6- to 10-Hz oscillations were generated throughout the network. These findings give further support to the hypothesis that Ih is critically involved in the generation of slow rhythmicity in synchronized thalamic activity.